PSYCHOLOGICAL PROFILE OF EMPLOYEES - VICTIMS OF MOBBING AT WORKPLACE (Annual of the Faculty of Philosophy in Skopje, 2012)
Mobbing is defined as the phenomenon of psychological harassment, which is repeated through activities in order to degrade the employee on different grounds. Mobbing causes the violation of human rights and dignity, and harms the physical and mental health and decreases future of professional victim.For the purposes of this study a questionnaire consisting of 25 questions to determine the presence of mobbing was designed and for the examination of personal characteristics of employees - victims of mobbing NEO-PI-R personality inventory was used (Costa & McRae). The survey was conducted during a period of six months from January 2011 to June 2011. The sample in the survey included 255 participants (82 men and 173 women) working in five different activities: administration (50), health and social work (54), education (52) industry (53) and army (46) only from Skopje, Macedonia.When it comes to descriptive analysis, can be noticed that the arithmetic mean of the presence of mobbing the entire sample was M = 45.05, which is higher than the median for the entire sample Mdn = 43,00, but lower than the theoretical arithmetical mean Mt=50,00.In consideration of descriptive data on the five dimensions ofpersonality it is necessary to bear in mind that theoretical arithmetic mean is M= 96,00. The highest score of the respondents indicate the dimension Conscientiousness (M = 106.78), which is almost identical to that dimension of Agreeableness (M = 106.78) and the lowest Neuroticism (M— 88.40).The results obtained using the Pearson coefficient of correlation show that there is a positive connection between the presence of mobbing and Neuroticism (r =,259, p
Keywords: MOBING; EMPLOYEES; PERSONAL CHARACTERISTICS